International Roundtable - K.H. (Refuge: Canada’s Journal on Refugees, 1981)
On the occasion of the official visit to Canada of the United Nations High Commissioner for Refugees, Mr. Poul Hartling, the Canadian Foundation for Refugees and the UNHCR hosted an international round table discussion on the subject of integration of refugees. Ten delegates from across Canada and delegates representing Denmark, France, Greece, Hong Kong,Norway, Spain, Sudan, the U.K., and the U.S. shared their experiences regarding initial reception, language acquisition, and cultural and emotional problems of refugees.